2017
DOI: 10.1002/ldr.2750
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers of land and water commodification: socio‐environmental controversies of large‐scale land acquisitions

Abstract: A growing number of regions in the developing world are targeted by transnational investors who are acquiring large amounts of land and natural resources. Driven by the increasing global demand for agricultural products, such investments are often considered an opportunity for economic development in the target country. However, there are concerns about the social and environmental impacts on local communities. In this brief review, we discuss some key socio‐environmental controversies surrounding large‐scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…The societal implications of this agrarian transformation include a variety of critical problems (D'Odorico, Rulli, et al, 2017), such as dispossession of traditional users and systems of production (D'Odorico & Rulli, ; De Schutter, ), evictions and forced migrations (Adnan, ; Feldman & Geisler, ; Siciliano, ), ethical concerns related to violations of human and land tenure rights (Anseeuw et al, ; Toft, ) with particularly negative impacts on women (Behrman et al, ; White, ), rise in social conflicts and dynamics of coercion (Dell'Angelo, D'Odorico, Rulli, & Marchand, ), and multidimensional impacts on rural livelihoods in developing countries (Davis et al, ; Oberlack et al, ).Through LSLAs, land can be put under productive use to the benefit of investors and local communities, arguably (De Schutter, ), because of “trickle down” effects on employment, and access to modern technology and markets (e.g., Chakrabarti & Da Silva, ). An often overlooked impact, however, is the land degradation and land use change associated with large‐scale land investors (e.g., D'Odorico, Rulli, et al, ). In fact, forests and savannas may be cleared to accommodate new mines or farmlands (D'Odorico, Rulli, et al, ).…”
Section: Globalization Of Food and Watermentioning
confidence: 99%
See 2 more Smart Citations
“…The societal implications of this agrarian transformation include a variety of critical problems (D'Odorico, Rulli, et al, 2017), such as dispossession of traditional users and systems of production (D'Odorico & Rulli, ; De Schutter, ), evictions and forced migrations (Adnan, ; Feldman & Geisler, ; Siciliano, ), ethical concerns related to violations of human and land tenure rights (Anseeuw et al, ; Toft, ) with particularly negative impacts on women (Behrman et al, ; White, ), rise in social conflicts and dynamics of coercion (Dell'Angelo, D'Odorico, Rulli, & Marchand, ), and multidimensional impacts on rural livelihoods in developing countries (Davis et al, ; Oberlack et al, ).Through LSLAs, land can be put under productive use to the benefit of investors and local communities, arguably (De Schutter, ), because of “trickle down” effects on employment, and access to modern technology and markets (e.g., Chakrabarti & Da Silva, ). An often overlooked impact, however, is the land degradation and land use change associated with large‐scale land investors (e.g., D'Odorico, Rulli, et al, ). In fact, forests and savannas may be cleared to accommodate new mines or farmlands (D'Odorico, Rulli, et al, ).…”
Section: Globalization Of Food and Watermentioning
confidence: 99%
“…An often overlooked impact, however, is the land degradation and land use change associated with large‐scale land investors (e.g., D'Odorico, Rulli, et al, ). In fact, forests and savannas may be cleared to accommodate new mines or farmlands (D'Odorico, Rulli, et al, ). Several studies have found that in Indonesia and Cambodia LSLAs are a preferential mechanism for deforestation, with rates of forest loss exceeding those in similar adjacent areas outside land concessions (Carlson et al, ; Davis, Yu, Rulli, et al, ).…”
Section: Globalization Of Food and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Lacking a legal guarantee for de-facto land rights can even lead to dispossession of land-explored by scholars as a human rights problem [2,3]. Also negative consequences beyond these areas need to be considered [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, there has been a rapid increase in large-scale land acquisitions to produce fibre, biofuels, feed and food for international markets, which has impacted ecosystems, agro-ecosystems and societies, predominantly across the Global South (D'Odorico et al 2017). Socio-environmental changes in the context of large-scale land acquisitions are highly complex and associated with several sustainability challenges, like deforestation (Davis et al 2015), water scarcity and pollution (Dell'Angelo et al 2018), soil degradation (Lazarus 2014) and food insecurity (Havnevik et al 2011).…”
Section: Introductionmentioning
confidence: 99%